الأحكام الدستورية الداعمة لاستقلالية القضاء في ظل التعديل الدستوري لعام 2020 - بن ناجي، مديحة (جامعة أحمد دراية أدرار, 2022)
نص المؤسس الدستوري الجزائري من خلال التعديل الدستوري 2020 على مواد جديدة تدعم استقلالية القضاء، ويظهر ذلك من خلال دسترة عدة ضمانات عضوية لاستقلالية القاضي والقضاء، كضمانات التعيين ومنح الطابع القضائي لتشكيلة المجلس الأعلى للقضاء، وبذلك منح استقلالية لهذا المجلس خاصة وأنه الجهاز الداعم والحامي لاستقلالية القاضي، بالإضافة إلى التأكيد على تحقيق الاستقلال الوظيفي للقضاة في هذا التعديل الدستوري بالنص صراحة على خضوع القاضي للقانون في الدستور وعدم قابلية القضاة للعزل والنقل والتأديب. Through the 2020 constitutional amendment, the Algerian constituent included new articles that support the independence of the judiciary. This approach can be demonstrated by several guarantees for the independence of the judge and the judiciary system. Such as the guarantees of appointment of the judge and vesting the judicial aspect to the members of the Superior Council of Magistracy. Particularly as it is the supporting and protecting body for the independence of the judge. In addition to highlighting the independence of judges in this constitutional amendment by explicitly stipulating the submission of the judge to the law and the inability of the judges to be dismissed, transferred and sanctioned.
Keywords: الدستور الجزائري -- الأحكام الدستورية -- المجلس الأعلى للقضاء